Enterprise one to one : tools for competing in the interactive age - Peppers, Don.; Rogers, Martha, 1952- (New York : Currency Doubleday, 1997)
Explains how businesses can use interactive information gathering to get a better idea of what their customers want and serve them better by anticipating their needs.
1. The Musical Condom: The Basic Rules of Competition Rewritten for the Interactive Age -- 2. Some Customers are More Equal than Others: How to Identify and Capitalize on Customer Differences -- 3. Mapping the Strategy: How to Use Your Customer Base to Map Out Your 1:1 Strategy -- 4. Infant Mortality at MCI: How to Fix the "Leaky Bucket" of Customer Attrition -- and How Not To -- 5. Growing Your Customer Base: How to Increase Your Share of Customer and Improve Your Bottom Line -- 6. The Asymmetrical Brassiere: How to Profit from Mass Customization -- 7. Smart Retreads: How to Keep Your Customers Forever, and Increase Your Margins Too -- 8. Expanding the "Need Set": How to Customize, Even if You're Selling a Commodity -- 9. Community Knowledge: How to Anticipate What Your Customer Wants -- 10. Surfing the Feedback Loop: How to Get More Customer Feedback While Protecting Privacy -- 11. The Medium is the Matchmaker: How to Own the Customer in a Changing Media Landscape -- 12. The Busy Shoe Salesman: How to Remove Distribution Barriers Between You and the Customer -- 13. Making It: How to Get There from Here -- 14. An Open Letter to the CEO.
Βιβλιογραφία: σ. 392-414.
Περιέχει ευρετήριο.
Keywords: Customer relations; Market segmentation; Relationship marketing; Πελατειακές σχέσεις -- Διαχείριση; Technological innovations; Customer relations; Customer relations; Datenverarbeitung; Kundenmanagement; Market segmentation; Market segmentation; Relationship marketing; Relationship marketing; Technological innovations; Technological innovations; Informatietechnologie; Klantgerichtheid; Wedijver